Implementation of Balanced Scorecard in An Airline Company in The Bandung District Area - Viasido Sarumpaet (PT Publikasiku Academic Solution, 2025)
This study aims to evaluate the performance of PT Merpati Nusantara Airlines (MNA) Bandung District through the application of the Balanced Scorecard, with particular emphasis on assessing the presence and maturity of a learning organization within the company. As MNA strives to enhance service quality and maintain a competitive position in the aviation industry, it becomes increasingly important to measure not only operational performance but also the company’s adaptability to evolving business conditions. Although PT MNA holds ISO 9002 certification - demonstrating established business processes - this research highlights the need for strategic management tools that align with the company’s vision and mission to drive accountability and measurable outcomes. In an era marked by digital transformation and the rise of e-commerce, the company must adopt an integrated management approach that supports ongoing performance evaluation and continuous development. Fostering a culture of learning within the organization is vital for navigating change and achieving both internal enhancements and external competitiveness. By examining MNA's current performance and the extent to which it embodies a learning organization, this study offers insights into the company’s preparedness to meet dynamic industry challenges. The findings are expected to inform improvements in strategic planning and operational effectiveness. Future research should delve deeper into how cultivating a learning organization impacts long-term success and competitive advantage.